But how? - Allencherril, Joseph (Ars Medica, 2015)
I’ve been putting my free-range eggs in the red wine basket and the olive oil basket and the whole grain basket And I’m jumping on the and the wild-caught oily salmon train and the dark chocolate train. I’m a health nut, an almond/weightlifting nut And I’m still on the gluten-free bandwagon as well as the organic one with a sprinkling of Ω-3 and vitamin D And you’re saying I have six months?